ETHNIC ELEMENT IN THE CONTEMPORARY GEORGIAN POSTMODERNIST INTELLECTUAL DISCOURSE (“ARILI” AND “DIDGORI” AS ACTORS OF “IMAGINED COMMUNITIES” AND “INVENTED TRADITIONS”) - Kircanov, Maksim Valer'evic (History, Archeology and Ethnography of the Caucasus, 2020)
The paper attempts to analyze collective ideas of ethnicity and ethnic culture in the modern intellectual discourse of Georgia in the context of interdisciplinary theories of nationalism. In the contemporary modernistic historiography nationalism is considered as a social and cultural construct and one of the consequences of modernization, which minimizes the factor of ethnicity, reduced to one of the invented traditions. The purpose of the article is to analyze various forms and dimensions of “ethnicity” and “ethnic” in modern Georgian cultural nationalism as a modernist and constructivist project. The author, using the methods of “imagined communities” and “invention of traditions” proposed in the modernist historiography of nationalism, and transplanting them into the contexts of the history of Georgian nationalism, suggests that 1) the modern project of nation in Georgia is based on the idea of Georgians as a political community and the actualization of the concepts of “kartveloba”; 2) Georgians are analyzed in terms of a political community, not a historical nation; 3) kartveloba is defined as an invented tradition, originated in intellectual discourse as a result of transplantation of western theories of nationalism. Therefore, the author, on the one hand, analyzes the role of ethnicity and ethnic culture as its institutionalized form, sanctioned by professional intellectuals as nationalists in the development of modern nationalist imagination in the contexts of the activities of Georgian intellectuals as the main inspirers of nationalist discourse, on the other hand, the author believes that 1) the Georgian intellectuals are active in their attempts to develop the concept of “kartveloba” as a synthetic, “imagined” or “invented” variant of the true Georgian identity; 2) they are not inclined to enthographize ethnic culture in the post-Soviet forms, rejecting the Soviet models of its museumification; 3) instead of an assimilative post-Soviet model of actualization of ethnic culture, Georgian intellectuals seek to revitalize and actualize it in the world of postmodernism and consumer society, which allowed us to synthesize the values of kartveloba as an ethnic culture and the principles of a nation as a political community. Thus, the author considers the Georgian model of the development of nationalism as a compromise: on the one hand, ethnic culture is represented in cultural spaces, while one the other hand intellectual transplantations of western culture do not exclude manifestations of Georgian ethnicity, facilitating its integration into the western canon.
Keywords: Georgia; intellectuals; ethnicity; ethnic culture; carteloba; actualization of ethnicity; nationalism